Effect of a Health-Education Program Based on the BASNEF Model of Overall Sexual Health Satisfaction and Satisfaction with Quality of Sexual Relationship among Women with Infertility - Shahbazi A; Behboodi Moghadam Z; Maasoumi R; Saffari M; Mohammadi S; Montazeri A (Dove Medical Press, 2020)
Azade Shahbazi,1 Zahra Behboodi Moghadam,1 Raziyeh Maasoumi,1 Mohsen Saffari,2 Saeed Mohammadi,1 Ali Montazeri3 1Reproductive Health Department, School of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran; 2Health Research Centre, Life Style Institute, Baqiyatallah University of Medical Sciences, Tehran, Iran; 3Population Health Research Group, Health Metrics Research Center, Iranian Institute for Health Sciences Research, ACECR, Tehran, IranCorrespondence: Azade Shahbazi; Ali Montazeri Email shahbazi.midwifery@gmail.com; montazeri@acecr.ac.irIntroduction: Female infertility is increasing in Iran, encompassing all dimensions of women’s lives. One of the most important effects of infertility is on sexual function. All women have the right to sexual health. Using educational models, one can see a positive effect on women’s sexual function. The present study aimed to investigate the effect of an education program based on the beliefs, attitudes, subjective norms, and enabling factors (BASNEF) model on promoting overall sexual health satisfaction and satisfaction with the quality of sexual relationships among women with infertility.Methods: This was a quasiexperimental study conducted on 80 infertile women referred to an infertility center affiliated with Tehran University of Medical Sciences, in Tehran, Iran in 2016– 2017. Infertile women with primary infertility were divided into experimental and control groups based on odd and even days. The intervention was carried out based on the BASNEF model over four sessions. Data were collected using a demographic questionnaire, the BASNEF questionnaire, and items on overall sexual health satisfaction and satisfaction with their sexual relationship. The questionnaires were completed before and 4 and 8 weeks after the intervention in the two groups. Friedman, χ2, and t-tests were used for data analysis.Results: After the educational intervention, BASNEF values and overall sexual function and satisfaction with the quality of sexual relationships had significantly improved in the experimental group (p< 0.05), while changes were not significant in the control group.Conclusion: The results showed that the BASNEF model–based educational invention improved overall sexual health and satisfaction among intertitle women. Indeed, it seems that using theory-based educational interventions in infertility centers might be helpful.Keywords: infertility, sexual function, female, reproductive health